Trans-European networks (TEN): future in the past? - Elena Kuznetsova (European Regional Science Association (ERSA), 2013)
The European Union hasbeen working out the unique transport strategy.Treaty on the Functioning of the European Union - (Articles 90 - 100) demonstrates that it should be common policy in the sphere of European transport. Since the Rome Treaty's entry into force in 1958, this policy has been focused on removing borders between Member States and thus contributing to the free movement of individuals and of goods. The transport industry represents significant and quite important part of the EU economy. It accounts for about 7% of European GDP. Approximately 5% of the EU's employeesare engaged in the sector. The importance of transport sector for regional economy is realized in strategic legal documents. The primary goal of the paper is to provide an economic analysis of current and former European legislation and policy in the sphere of transport. To reach the goal we put three tasks: the consideration of the EU's basic concepts, making its' comparative analysis and evaluating its' influence for neighborhood countries (case of Russian Federation) There were several programs for implementing these issues for real economic situation. The key strategies in transport sector are depicted in the official program documents under the title White Paper. There were several editions of the document. White paper of 1992 bring in practice the term 'international transport corridor', which was later become very popular and of wide using. In 1994 the conference of the European transport ministers was held and had resulted in beginning of creation of Pan-European transport corridors, 3 from which were gone through Russia. The most significant and detailed was White paper of 2001which had presented itself a type of a program for further 10 years.The document identified as main challenges the imbalance in the development of the different transport modes, congestion on routes and cities, as well as in airspace, and the impact on the environment. Accordingly, the White Paper proposed policies to adjust the balance between the modes, stressed the need to do away with bottlenecks in the trans-European networks (TEN) and to reduce the number of road accidents, it called for an effective policy on infrastructure charging and it argued that the Community should strengthen its position in international organizations. According the enlargement of the EU and accession of new member-states the situation in the transport sphere has changed. New members should lead to the same level of infrastructure's development and transport situation in their countries. To answer to new possibilities and threats a new policy was implemented by High Level Group. There were approved 5 transport axes, which have linked Europe with other regions of the world. Today the work for improving transport situation and infrastructure in the EU isn't finished, but the great part of it is already done. Last White Paper was adopted in 2011. Nowadays it is in force. The White Paper is focused on the realizing joint intermodal projects, resolving some problems of transport nodes. National and regional officials, business actors from the EU and neighborhood states are involved in the process. Russian participation in the EU projects is supported by different agents of transport market. Both Russian commodities and passengers flows will be able revive regional transport infrastructure.
Keywords: 330; European legislation; transport policy; Russian participation in the EU transport projects